Stone Columns in Extremely Soft Soils in Scandinavia - Saleh, Khadeen (My University, 2024)
Stone columns are a well-established technique for improving the properties of soil under the foundation of embankments and heavy structures. Stone columns are inclusions of granular material typically installed using vibratory-displacement or vibro-replacement methods. A notable advantage of stone columns is that they tend to have a minimal impact on the properties of the surrounding soil, unlike other ground improvement methods. The primary outcomes of stone columns in untreated soil conditions include improved bearing capacity, reduced total and differential settlements, accelerated consolidation, enhanced stability of embankments and natural slopes, and decreased liquefaction susceptibility. Stone columns function as inclusions that provide higher stiffness, shear strength, and permeability than the natural soil. This enables them to effectively support the structure or embankment without significantly altering the physical state of the surrounding soil, as well as improve the drainage. The research aims to examine whether stone columns can be used in the soft clays typical to Scandinavia, resulting in preliminary design graphs. The numerical simulations will be carried out using constitutive models such as Creep-SCLAY1S and Soft Soil under 2D axisymmetric conditions in Plaxis. The simulations will be done as fully coupled consolidation concerning typical soil characteristics in Scandinavia. Ultimately, the outcome of this study would include Priebe-type charts suitable for Scandinavian clay, which can assist designers in constructing stone columns in each area. The findings reveal a substantial effect of the chosen constitutive model, the influence of replacement ratio A/Ac (the ratio of the area of the stone column to the area of the soil it replaces), and the effective friction angle of the stone column material on the settlement improvement factor. Furthermore, the results confirm and build upon previous findings, indicating that creep and increasing lateral earth pressure K increase the settlement improvement factor. Consequently, the results can be applied in stone column design for highly soft clay conditions (such as Swedish soil), where using Priebe’s charts might not be applicable.
Keywords: creep; extremely soft soil; friction angle; replacement ratio; creep-SCLAYL1S; settlement improvement factor; soft soil; Soft Soil-creep; stone-columns